Load- Carrying capability evaluation by the method of envelope equations (Journal of Science and Technology, 2016)
Envelope equations have been developed to provide a simple method for evaluating the load-carrying capability of process components such as found in nuclear and Petro-chemical plants. The use of the equations eliminates the, other-wise, elaborate and time-consuming analyses required to determine whether or not a given set of loads could be successfully applied to a specific structure. In particular, the equations are suitable for the evaluation of the different service code criteria such as those of the ASME.The method provides conservative upper bounds for the loads that a given structure can carry under a specified service condition. Thus, the equations could provide useful guidelines at the preliminary design stage to be backed later by more elaborate calculations for ultimate verification. Sample calculations are also presented to verify the validity of the equations.